2015
DOI: 10.4103/0255-0857.150909
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm as a virulence marker in Candida species in Nosocomial blood stream infection and its correlation with antifungal resistance

Abstract: Nosocomial blood stream infections (BSI) due to fungi especially Candida is increasing steadily. A two year prospective study was conducted in the S.C.B. Medical College with an aim to evaluate the species distribution, antifungal susceptibility and biofilm formation of Candida spp. isolated from nosocomial BSIs. 34 Candida spp. were isolated from 359 blood cultures. Antifungal susceptibility was performed by microbroth dilution technique and both visual and spectrophotometric method were used for biofilm dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 14 publications
6
19
0
Order By: Relevance
“…In the last few years, occurrence of NAC species is steadily increasing. In the present study, NAC accounted for 70% similar to studies by Oberoi et al, [11] 83.2% and Bhatt et al, [12] 85.3%. Over the past 20 years, a shift toward NAC species has been reported previously from the USA, Europe, and Australia although the precise pattern of causative species varies across countries.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the last few years, occurrence of NAC species is steadily increasing. In the present study, NAC accounted for 70% similar to studies by Oberoi et al, [11] 83.2% and Bhatt et al, [12] 85.3%. Over the past 20 years, a shift toward NAC species has been reported previously from the USA, Europe, and Australia although the precise pattern of causative species varies across countries.…”
Section: Discussionsupporting
confidence: 91%
“…Secondary resistance in C. albicans is primarily due to a decrease in the activity of the uracil phosphoribosyltransferase. [27][28][29] Our study showed 81% sensitivity to flucytosine which was similar to 63% by Bhatt et al [12] and 88.5% by Vinodkumar et al [30] The incidence of amphotericin B-resistant Candida spp. in our study was 13% which is comparable to incidences reported in recent studies.…”
Section: Discussionsupporting
confidence: 83%
“…And as reported by other authors, the MIC obtained in this study regarding flucytosine in the 15 strains analyzed is high compared to that reported by Silva et al, [3] Miranda et al, [2] and Canton et al [17]. These reports were obtained in studies conducted in Europe, while in India, Bhatt M et al [22]obtained high rates of FLC resistance in C. parapsilosis isolates.…”
Section: Discussionsupporting
confidence: 71%
“…However, Shin et al [23] reported C. tropicalis was most common isolates followed by C. parapsilosis, C. glabrata, and C. albicans. While, another study by Bhatt et al [29] reported C. parapsilosis and C. tropicalis were strong biofilm producers whereas C. albicans and C. krusei were identified as weak producers.…”
Section: Discussionmentioning
confidence: 95%
“…Yet, glucose is thought to serve as the carbohydrate energy source required by Candida for biofilm formation [25], perhaps necessary to produce the polysaccharide matrix [27], in which organized communities of yeast, hyphae, and pseudohyphae are enclosed [28]. In a study by Bhatt et al [29] they reported administration of broad spectrum antibiotics, indwelling catheter and patients on mechanically ventilator were the major risk factor.…”
Section: Discussionmentioning
confidence: 99%